Karakteristik Kimia Selai Kacang Tersubstitusi Kenari - Samponu, Maria M F; Moniharapon, Erynola; Tuhumury, Helen C D (Jurnal Agrosilvopasture-Tech, 2023)
The purpose of this study was to determine the effect and characteristics of canarium nut-substituted peanut butter. This study was designed using a one-factor complete randomized design, namely the substitution of peanuts with canarium nuts with five treatment levels of 0% canarium nuts : 100% peanuts, 25% canarium nuts : 75% peanuts, 50% canarium nuts : 50% peanuts, 75% canarium nuts : 25% peanuts, and 100% canarium nuts : 0% peanuts replicated twice. Observed variables include moisture content, ash content, protein content, fat content, and carbohydrate content. The results showed that the more canarium nuts used for peanut substitution in peanut butter, the lower the moisture content (3.93–1.21%) and protein content (24.70–10.10%), while the ash content (1.51-2.43%), fat content (37.95–53.36%), and carbohydrate content (18.32–46.52%) increased.